The Role of Electronic Worth of Mouth in Mediating TikTok Social Media Toward the Organizational Image of Universitas Muhammadiyah Ponorogo - Eka Destriyanto Pristi A.; Fery Setiawan; Titis Purwaningrum (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2022)
The use of social media as a new medium in marketing has been considered quite effective. The users obtain plenty of marketing benefits through social media. TikTok social media has been recently famous amidst the society. This social media with a short video has the advantages to draw the attention of the viewers. The use of social media in marketing creates comments in the form of E-WOM which enables it to impact the image of an organization or company. This research uses a quantitative research method, taking 100 members of the campus tour of Universitas Muhammadiyah Ponorogo in 2021 as the sample. The marketing strategy using social media is executed by the technical implementation unitÂ  of the new student admissions of Universitas Muhammadiyah Ponorogo by creating a short video uploaded in its Instagram account. The organizational image becomes a dependent variable of this research which will be tested by the use of TikTok as an independent variable and E-WOM as a mediator variable. The result of this research shows that E-WOM has a positive influence in mediating the impact of TikTok use toward the organizational image of Universitas Muhammadiyah Ponorogo.Â